1994
DOI: 10.1136/gut.35.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of the long term outcome in gastro-oesophageal reflux disease: six year follow up of 107 patients.

Abstract: There is little information concerning the long term outcome of patients with gastrooesophageal reflux disease (GORD). Thus 109 patients with reflux symptoms (33 with erosive oesophagitis) with a diagnosis of GORD after clinical evaluation and oesophageal testing were studied. AU patients were treated with a stepwise approach: (a) lifestyle changes were suggested aimed at reducing reflux and antacids and the prokinetic agent domperidone were prescribed; (b) H2 blockers were added after two months when symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
2
16

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(65 citation statements)
references
References 26 publications
2
45
2
16
Order By: Relevance
“…2 Kuster and co-workers found that a low LES resting tone predicted a need for long-term therapy with H 2 -receptor antagonists or anti-re¯ux surgery. 8 In the present study, however, neither severity of gastrooesophageal re¯ux nor LES tone seemed to predict time to relapse. Gastric acidity was a signi®cant predictive factor, possibly due to duodenogastric re¯ux, which is more common in patients with more severe re¯ux disease.…”
contrasting
confidence: 46%
See 1 more Smart Citation
“…2 Kuster and co-workers found that a low LES resting tone predicted a need for long-term therapy with H 2 -receptor antagonists or anti-re¯ux surgery. 8 In the present study, however, neither severity of gastrooesophageal re¯ux nor LES tone seemed to predict time to relapse. Gastric acidity was a signi®cant predictive factor, possibly due to duodenogastric re¯ux, which is more common in patients with more severe re¯ux disease.…”
contrasting
confidence: 46%
“…6,7 Lower oesophageal sphincter (LES) tone has been considered an important determinant for competence of the cardia and in predicting long-term outcome. 2,8 Gastric Helicobacter pylori infection is probably not a causal factor in re¯ux oesophagitis, but is thought to affect response to acidsuppressive therapy with omeprazole. 9,10 We set out to consider the predictive value of these data in assessing time to endoscopic and/or symptomatic relapse in patients on maintenance treatment with the proton pump inhibitor lansoprazole.…”
Section: Introductionmentioning
confidence: 99%
“…13±18 However, similar studies of the risk of relapse after cessation of treatment, 14,17 or during maintenance treatment, have shown con¯icting results regarding the importance of the severity of oesophagitis as a predictor for relapse. 28,29,40,41 This was therefore a major focus of our analysis. The sensitivity of this evaluation was affected by the use of two systems for grading of the severity of re¯ux oesophagitis within the ®ve studies evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, lower oesophageal sphincter pressure and grade of oesophagitis, which have been identi®ed by others as useful indicators of outcome, did not have any prognostic value. 5,10,14,25 It could be argued that this study has not demonstrated whether or not cisapride prevents endoscopic relapse. However, if a patient's symptoms have relapsed to the extent that the patient requests further therapeutic intervention (as in this study), then in clinical practice this is a failure of therapy regardless of whether or not endoscopy shows a return of oesophageal erosions.…”
Section: Discussionmentioning
confidence: 99%